Yoram Hazony and Leo Strauss on the Relation between Philosophy and Revelation. (2nd July 2016) - Schaefer, David Lewis
ABSTRACT: This essay challenges Yoram Hazony's ostensible correction of Leo Strauss's account of the tension between philosophy and revelation in Hazony's book The Philosophy of Hebrew Scripture . While Hazony persuasively demonstrates the value of the Hebrew Bible, notably the half that he calls the "History of Israel, " as a work of rational political theory, emphasizing the difference in function between the Torah and the Christian "New Testament" (which serves chiefly to "bear witness" to particular events, rather than account for the permanent character of human and political life), he wrongly accuses Strauss of sharing the position of the radically antiphilosophic Christian theologian Tertullian that the Bible and classical philosophy are "absolutely oppos[ed], " even though Strauss, unlike Tertullian, takes the side of philosophy rather than the Bible in this conflict. Contrary to the impression Hazony conveys, Strauss readily acknowledged that the believer, no less than the philosopher, is obliged to make use of reason in his quest for truth and noted the critical areas of agreement between the Torah and classical philosophy. He simply emphasized the conflict between philosophy's reliance on reason as the ultimate guide to truth and the dependence of the Bible on belief in divine revelation, a dependence that Hazony implausibly seems to deny. And Hazony's challenge to the very distinction between reason and revelation threatens to weaken our appreciation of both sides of this tension, which Strauss identified as the source of the West's "vitality."